Medial Radial Head Dislocation Associated with a Proximal Olecranon Fracture: A Bado Type V?. (17th March 2014) - Segaren, Neil; Abdul-Jabar, Hani B.; Segaren, Nicholas; Barry, Matthew
Abstract : The Monteggia fracture is relatively rare. We present an unreported configuration of a traumatic olecranon fracture with a concomitant medial radial head dislocation in a 3-year-old male. This injury was initially missed and required a subsequent operative intervention. Following surgery, there was evident fracture union, articular congruency, and a full functional recovery. Medial radial head dislocation is not accounted for in the Bado (1967) classification of the Monteggia lesion and hence we propose the addition of a Bado V category.